Using Flexible Loans to Improve Access to Credit for Farmers in Kenya - Onyango, Fredrick; Upadhyaya, Radha (Academia Kenya, 2021)
ending to the agricultural sector in Kenya is low. According to a report by the Kenya Bankers Association (KBA), only four percent of commercial banks’ lending goes into agriculture (KBA, 2018). Most of these loans go to large farmers as smallholder farmers are unable to meet banks’ requirements as well as the stringent repayment terms demanded by banks. Thus, smallholder farmers have to rely on other sources of finance for farm financing. As Kenya seeks to achieve the food security goal as enshrined in Vision 2030, it is increasingly important to finance smallholder farmers in order to improve agricultural production and productivity and transform the rural economies. Given that farmers do not have regular incomes, making regular repayments from agriculture is untenable. Some lenders, especially microfinance lenders, have designed loan products that offer farmers some flexibility in repayment. Such loans mostly contain features such as grace periods and flexible repayment schedules. Other features include bullet/balloon payments, loan refinancing, loan rescheduling, and credit lines. Flexible loans are expected to be attractive to farmers given that they usually match the cash flows of farmers. Thus, access to credit is expected to improve when loan products are designed with flexible terms. This has been a subject of debate among scholars.
Keywords: Agriculture; Kenya